(untitled) (One Health Journal of Nepal, 2024)
Established in 1988, Nepal’s Female Community Health Volunteers have been on the front lines of promoting family planning and maternal health through community engagement. From an initial role in distributing birth spacing products, FCHVs have evolved in their responsibilities over the past three decades to take on leading Health Mothers’ Groups and addressing a wide array of public health issues. There has been reasonable progress in the reduction of maternal and child mortality. This article will be focused on the increasing burden of NCDs, particularly CVD, in Nepal, where limited resources exist for its management. FCHVs reflect a promising, underutilized resource for community-level NCD care. Using available evidence and targeted training in the prevention of NCDs and CVD risk screening would help reduce the burden of NCDs through the preventive services delivered by FCHVs. This viewpoint aims to explore the potential of integrating FCHVs for strategies for prevention of NCDs and the need for adapting training programs.